ANALYSIS OF THE EFFECT OF LIQUIDITY, SOLVENCY, AND PROFITABILITY ON SHARE PRICES IN LQ45 COMPANIES - Muhammad Akbar (International Journal Labs, 2024)
This study aims to determine and analyze the effect of Liquidity, Profitability and Solvency through proxy Current Ratio, Retunr on Asset and Debt to Equity Ratio on Share Prices in LQ45 companies listed on the Indonesia Stock Exchange for the period 2017 – 2019. The population in this study is LQ45 companies with a sample used in this study as many as 26 companies, the data used was obtained from the financial statements of each company. The approach method used in this study is quantitative method with panel data regression. The results showed that Liquidity (Current Ratio) has no influence on stock prices, while Profitability (Return on Assets) and Solvency (Debt to Equity Ratio) partially have an influence on stock prices / returns